Elaboração e aplicação de uma estratégia de ensino sobre os conceitos de calor e de temperatura - Rafael, Francisco Josélio (2007)
This piece of work has investigated the alternative conceptions shown by students of secondary school, concerned to the concepts of warmth and temperature, aiming the elaboration and application of a learning strategy as of the diagnose risen from the conceptions present in students. The learning strategy was built up by a sequence of activities that involve History of Science and experiments, put in a course that had as a base the proposal of the Group of Redevelopment of Physics Teaching (GREF). We have used as the conductor wire of our research the development of thermo dynamics since the development of the first thermo machines, passing by the Industrial Revolution and the evolution of concepts of warmth and temperature. The learning strategy was applied to a group of second grade of secondary school in a public school in Mossoró (RN). By doing these activities we tried to become the concepts, which are part of thermo dynamics, more meaningful to the students. We have estimated that the application of the strategy has represented some profits to the students of the group, concerning to learning of laws and concepts of thermo dynamics (specifically the concepts of warmth and temperature), as well as what it is referred to the overcoming of its initial conceptions